Prevalensi dan Dampak Kecanduan Gadget Pada Remaja: Literature Review - Mentari Kusuma Rini; Titih Huriah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: To know the prevalence and impact of gadgets addiction on youth. Method: The method utilized in this paper was a literature review of international journals conducted using the PubMed, ProQuest, Goggle Scholar database. At the initial stage of the search with the keywords: